2018 Langley Award for Basic Research on Nicotine and Tobacco: Bringing Precision Medicine to Smoking Cessation. Issue 2 (10th April 2019) - Bierut, Laura J
Abstract: Introduction: Large segments of the world population use combustible cigarettes, and our society pays a high price for smoking, through increased healthcare expenditures, morbidity and mortality. The development of combustible cigarette smoking requires the initiation of smoking and a subsequent chain of behavioral transitions from experimental use, to established regular use, to the conversion to addiction. Each transition is influenced by both environmental and genetic factors, and our increasing knowledge about genetic contributions to smoking behaviors opens new potential interventions. Methods: This review describes the journey from genetic discovery to the potential implementation of genetic knowledge for the treatment of tobacco use disorder. Results and Conclusions: The field of genetics applied to smoking behaviors has rapidly progressed with the identification of highly validated genetic variants that are associated with different smoking behaviors. The large scale implementation of this genetic knowledge to accelerate smoking cessation represents an important clinical challenge in precision medicine.